Knowledge gaps in AR6 around Livestock in Africa - Cramer, Laura K. (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
Climate change impacts on livestock are already occurring - Encroachment by woody plants on key grazing lands, reducing fodder availability (NA, EA, CA, WA, SA) - Decreases in dairy production due to high temps and high relative humidity (NA) - Increased livestock mortality and livestock price shocks related to droughts (NA, EA, CA, WA) - Increased temps and rainfall expanding range of tick species that spread economically harmful diseases (EA, SA)